Metode Pembentukan Akhlakul Karimah Dalam Forum Annisa di SMAN 1 Panti Pasaman - Mei Derfi; Fauzan Fauzan; Januar Januar; Eka Rizal (Universitas Maritim AMNI Semarang, 2023)
This research is motivated by a significant change in the morals of classs XI students for the better after participating in the annisa forum within 1 year at SMAN 1 Panti Pasaman. With indicators of changes in morals, namely morals towards oneself, changes in dressing more modestly the hijab covering the chest according to school regulations, morals towards others by behaving well and speaking more politely, to others, as well as morals towards Allah SWT, namely being more diligent in praying and reading al-qur’an. The purpose of this research is to find out what are the method of forming akhlakul karimah in the annisa forum at SMAN 1 Panti Pasaman. This research uses field research with a qualitative descriptive approach. The research informants were the key informants, the teacher who built the Annisa forum and the informant who supported the class XI female students. Data analysis techniques using data reduction, data display, drawing conclusion. The results of the research show that the method of forming akhlakul karimah in the annisa forum at SMAN 1 Panti Pasaman has been implemented, through the lecture method accompanied by inspiring historical stories of the prophet, singing kasidah, and motivating rhymes, the question and answer method by giving students the opportunity to ask or Answer questions so that the students are more understanding the lecture material, the exemplary methods in terms of appearance and dress, time discipline, behave and speak, the affection methods by giving sincere and sincere attention, the advice methods by giving good advice, the habituation methods by getting used to saying basmalah, greetings obligatory prayers, midday prayer system (prayer agenda), and reading and memorizing the Qur’an, reward methods in the form of praise, smiles, applause, and the form of baranf, namely the qur’an for female students who are have an achievement, as well as methods of punishment methods in the form of advice, a letters of agreement, and a monetary fine according tho the agreement between the female students and the teacher for female students who deliberately do not participate in the Annisa forum without any clear reason. The change in the students morals for the better indicates the success of implementing the akhlakul karimah of class XI female students in the Annisa forum at SMAN 1 Panti Pasaman.